2018
DOI: 10.1101/336933
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Cerebral Blood Flow after single dose of antipsychotics in healthy volunteers depends on dopamine D2 receptor density profiles

Abstract: As a result of neuro-vascular coupling, the functional effects of antipsychotics in human brain have been investigated in both healthy and clinical populations using haemodynamic markers such as regional Cerebral Blood Flow (rCBF). However, the relationship between observed haemodynamic effects and the pharmacological action of these drugs has not been fully established. Here, we analysed MRI-based rCBF data from a placebo-controlled study in healthy volunteers, who received a single dose of three different D2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…Interestingly, we also observed DA–BOLD associations in extrastriatal areas. This finding is in line with a recent study showing that both D 2 and D 3 receptor antagonists and agonists modulate blood flow changes in cortical areas (Black et al, 2002; Selvaggi et al, 2018; van den Brink et al, 2018). Indeed, it is well documented that dopaminergic terminals are located close to the cortical microvasculature and in vivo administration of DA causes a vasomotor response (Krimer et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we also observed DA–BOLD associations in extrastriatal areas. This finding is in line with a recent study showing that both D 2 and D 3 receptor antagonists and agonists modulate blood flow changes in cortical areas (Black et al, 2002; Selvaggi et al, 2018; van den Brink et al, 2018). Indeed, it is well documented that dopaminergic terminals are located close to the cortical microvasculature and in vivo administration of DA causes a vasomotor response (Krimer et al, 1998).…”
Section: Discussionsupporting
confidence: 93%
“…The link between D 2 neuroreceptor distribution, drug action and brain function, evaluated as changes in CBF, was also investigated in the context of antipsychotics: Given a single effective dose of an antipsychotic, an increase in striatal CBF was found that could also be correlated with receptor distribution and DRD2 mRNA expression profiles. 69 Consistent with other pharmacological studies, all four investigated antipsychotics showed a spatial neurovascular coupling to baseline receptor density profiles. A similar study that investigated seven clinical drugs relevant in psychiatry showed that coupling between receptors and neurovascular responses is applicable to several receptor targets.…”
Section: The Dopamine Systemsupporting
confidence: 87%
“…The strongest effects observed with low dose rather associate with DAT, SERT and D1 receptor maps. In our previous study (Selvaggi et al, 2018) we observed correlations with D2 receptors at both doses for the group averaged data. This study did not examine effects using other targets and did not evaluate individual differences.…”
Section: Conclusion From the Application Examplesmentioning
confidence: 51%
“…While providing information about the spatial location of respective signals, such analyses do not allow drawing conclusions on potential neurophysiological mechanisms underlying the observed associations. To overcome this limitation, several recently published studies made use of spatial associations between underlying biology and observed imaging alterations by correlating ex vivo micro RNA spatial expression patterns with different imaging measures (Liu et al, 2019; Rizzo, Veronese, Expert, Turkheimer, & Bertoldo, 2016; Selvaggi et al, 2018). The major idea behind such analyses is that disease‐ or drug‐induced changes in imaging measures occur in association with availability of a specific tissue property (i.e., expression of a specific receptor) that is affected by the respective condition.…”
Section: Introductionmentioning
confidence: 99%